A fluorescent probe for benzenethiols and its application on test paper, in water samples and living cells1. Issue 31 (21st August 2015) - Zhang, Wenying; Liu, Xingjiang; Zhang, Hongyan; Feng, Chengcheng; Liu, Chunxia; Yu, Mingming; Wei, Liuhe; Li, Zhanxian
<x xml:space="preserve">Abstract</x> Using the selective cleavage of 2, 4-dinitrobenzenesulfonamide by benzenethiols, a 1, 8-naphthalimide-based OFF-ON fluorescent probe was synthesized and its application was demonstrated.